Holocene vegetation dynamics on the Bolshoi Ainov Island (Barents Sea, Russia) as a reflection of land uplift and the seabird influence - Filimonova, Ludmila V.; Kutenkov, Stanislav A. (Nature Conservation Research: Заповедная наука, 2025)
An abundant and diverse vegetation, presence of extensive cover peatlands and the habitat of a large number of seabirds distinguish the Ainov Islands (Kandalaksha State Nature Reserve, Russia) from most other Arctic islands and nearby mainland areas of the Kola Peninsula, considering them an attractive object for paleoecological reconstructions. A considerable decrease in size of Fratercula arctica colonies, resulted in land cover changes, makes this research particularly relevant. Obtained data on dependence of composition and formation of plant communities on various environmental conditions can help in assessing the significance of processes currently occurring in northern marine ecosystems and in predicting further transformations of the Arctic biota. Stratigraphic, radiocarbon and paleobotanical (pollen, spores and plant remains) studies of the peat deposit section of the upper plateau crowberry heath have been carried out to reconstruct the vegetation development history of the Bolshoi Ainov Island. The reconstruction based on the principles of actualism uses obtained and available published data on the modern floristic composition. The vegetation development is considered from the island formation time ca. 5000 calendar years before the present (hereinafter – cal BP) to the present. Its main directions are from obligate halophytes sparse communities and coastal meadows formation to tundra-like crowberry heaths on convex landforms and to grass-moss mires in depressions. Presence of ornithogenic vegetation and fern thickets is specific to the island and reflected in the palynospectra. On the first stages, three-level coastal meadows form as a result of the island uplift. The peat deposition started ca. 3940 cal BP in their upper part in the «boundary» communities, which, along with herbs, included dwarf shrubs, Rubus chamaemorus and Chamaepericlymenum suecicum. A coastal meadow strip with ornithogenic vegetation shift down from the island upper plateau, following the sea regression and crowberry heaths, began to form ca. 3100 cal BP. The herbaceous-dwarf shrub peat and later dwarf shrub peat began to accumulate with average vertical growth of 0.34 mm/year. In the Sub-Atlantic period, since ca. 2460 cal BP the crowberry heath expansion has continued. Currently the Bolshoi Ainov Island, with the exception of the coastal zone, is completely covered with peatland, the depth of which on the upper plateau reaches 120–132 cm. Seabirds have had a considerable influence on the Bolshoy Ainov island vegetation from the beginning of its formation till the present, as evidenced by the bird feather fragment presence in the deposit, the increased content of macroremains and pollen of herbaceous plants in peat, as well as their taxonomic composition. The abrupt shift in dominance of dwarf shrubs to herbs in the pollen diagram since 1800 cal BP has been explained by the development of a major colony of Fratercula arctica. It was facilitated by the formation by this time of dry and fairly deep extensive peatland suitable for burrowing. The Fratercula arctica colony size experienced fluctuations, which was reflected in the alternation of pollen maxima of Asteraceae, Rumex and some other herb taxa. An increase in Empetrum pollen content along with the Asteraceae proportion decrease in the palynospectra formed the last 100–200 years reflects considerable decrease in the number of Fratercula arctica individuals, the overgrowing of abandoned colonies, and the restoration of crowberry heaths. This paper shows the possibility of using modern floristic composition data to reconstruct the stage-by-stage formation of the vegetation cover on the Bolshoy Ainov Island, which may well be applied to other isolated territories. Palynological data complemented the results of macrofossil analysis of peat, allowing us to resolve the issue of undetectable herbaceous macroremains and more accurately reconstruct the initial stages of peat formation. The identified alternation of pollen maxima of ornithogenic pressure intensity indicator plants made it possible to put forward a hypothesis about periodic fluctuations of bird colonies caused by Holocene climate changes. To verify this, clarify the time and reasons, it is necessary to continue research in order to obtain confirmatory paleobotanical material and AMS dating. It is also promising to use other markers along with palynological markers, including heavy nitrogen isotopes.